PENGARUH PENGGUNAAN VARIASI PERANGKAP HAMA TERHADAP SERANGAN KUMBANG TANDUK (Oryctes rhinoceros,L.) UNTUK PENGENDALIAN HAMA PERKEBUNAN KELAPA SAWIT - SHIHAB, M RIZKI; Sutanto, Agus; Widowati, Hening (BIOLOVA, 2024)
Oil palm (Elaeis guineensis Jacq.) is the main plantation commodity in Indonesia. In the development of oil palm growth. Problematic and influential pests in the growth of oil palm, namely the horn beetle Oryctes rhinoceros, L. The low level of public knowledge regarding the control of the horn beetle Oryctes rhinoceros, L. has caused plantations to decline. This research intends to find out the differences in the use of variations of pest traps to total beetle pests. This research is an experimental research. The object of this research is the beetle traps made with 3 types, namely derigen traps, funnels, and buckets. This research test was assisted by utilizing pheromones, so that the horn beetle is easily trapped because it carries hormones to attract the horn beetle Oryctes rhinoceros L.. The results of data analysis showed that Oryctes rhinoceros L. was trapped in four monitoring times. Making several varied catches, namely 43 funnels, 41 drigens and 53 buckets. Based on data analysis using Anova Sig. (P-value) = 0.036 P is the value obtained. Thus at the significance level = 0.05 rejecting Ho, the conclusion obtained is that there is an important difference in the average of the three media used in the experiment.